2002
DOI: 10.1029/2001gl014157
|View full text |Cite
|
Sign up to set email alerts
|

Return of the cold halocline layer to the Amundsen Basin of the Arctic Ocean: Implications for the sea ice mass balance

Abstract: [1] CTD measurements from the Arctic Ocean 2001 expedition reveal that the cold halocline layer (CHL) has returned to the Amundsen Basin at a position close to that found during the Oden'91 expedition. River water from the Siberian shelves formed a strong freshwater front in the Amundsen Basin, extending from the Gakkel Ridge to the Lomonosov Ridge. Furthermore, we show from model computations that the presence of a CHL may increase winter sea ice growth by 0.25 m over one season compared to a case with a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 13 publications
(20 reference statements)
5
54
0
Order By: Relevance
“…Furthermore, our finding that negative NAO forcing caused the CHL to readvance toward its original position supports the observed return of the CHL to the Amundsen Basin in 2001 (Bjö rk et al 2002), following a period in the late 1990s and early 2000s when the NAO was more neutral in state.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, our finding that negative NAO forcing caused the CHL to readvance toward its original position supports the observed return of the CHL to the Amundsen Basin in 2001 (Bjö rk et al 2002), following a period in the late 1990s and early 2000s when the NAO was more neutral in state.…”
Section: Discussionsupporting
confidence: 71%
“…Atlantic Water (AW) entering the Arctic via the Barents shelf and West Spitzbergen Current (WSP) have warmed since the early 1990s, producing temperature anomalies in the Nansen Basin of roughly 118C in 2004 (Polyakov et al 2005). The increased penetration of AW caused the cold halocline (CHL) to retreat from the Amundsen Basin to the Makarov Basin in the mid-1990s (Steele and Boyd 1998), although measurements showed that it had returned to the Amundsen Basin in 2001 (Bjö rk et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Low salinities at the surface immediately below the sea ice cap may be a consequence of several processes, including sea ice melting cycles; inflow of water from the Pacific Ocean via the Bering Strait, which is fresher than the North Atlantic waters (Jones et al, 2008); and continental runoff primarily from the Siberian shelves (Björk et al, 2002). In our study, the halocline caused pronounced stratification, which varied due to the thaw-freeze cycle of sea ice and important freshwater inputs (Carmack and Wassmann, 2006).…”
Section: Regional Settingsmentioning
confidence: 78%
“…Thus to sustain a baroclinic geostrophic flow, the unobserved zone near the coast must have contained even fresher water than measured at the innermost station in the section. This would require surface salinities well below 32, which even during summer are rarely observed in the Arctic Ocean north of Fram Strait (Björk et al, 2002). Accordingly, we consider it unlikely that there were strong baroclinic flows near the coast.…”
Section: Discussionmentioning
confidence: 99%